1998
DOI: 10.1063/1.477403
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio study of specific solvent effects on the electronic coupling element in electron transfer reactions

Abstract: Specific solvent effects on the electronic coupling element for electron transfer are examined using two model donor-acceptor systems (Zn 2 ϩ and Li 2 ϩ ) and several model ''solvent'' species (He, Ne, H 2 O, and NH 3 ). The effects are evaluated relative to the given donor-acceptor pair without solvent present. The electronic coupling element (H ab ) is found to depend strongly on the identity of the intervening solvent, with He atoms decreasing H ab , whereas H 2 O and NH 3 significantly increase H ab . The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 68 publications
(51 reference statements)
2
30
1
Order By: Relevance
“…28,29 None of the coupled molecular dynamics/quantum mechanical studies discussed above considers all-electron models for the solvent. Our previous ab initio results 23 suggest that this may be a significant omission. Although the geometries examined in our studies were idealized, we found little orientation dependence for the superexchange effects induced by water, and we obtained evidence to suggest that water's effects were due largely to hole-type superexchange (i.e., the electronic coupling was propagated to a large degree through the occupied orbitals of water).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…28,29 None of the coupled molecular dynamics/quantum mechanical studies discussed above considers all-electron models for the solvent. Our previous ab initio results 23 suggest that this may be a significant omission. Although the geometries examined in our studies were idealized, we found little orientation dependence for the superexchange effects induced by water, and we obtained evidence to suggest that water's effects were due largely to hole-type superexchange (i.e., the electronic coupling was propagated to a large degree through the occupied orbitals of water).…”
Section: Introductionmentioning
confidence: 92%
“…23 In the ab initio results the systems were described using complete active space self-consistent field (CASSCF) wave functions; 40 the calculations were performed using MOLCAS 3. 41 Since ) for Zn2 + with (solid line, circles) and without (dashed line, squares), water present.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
See 3 more Smart Citations